Hvordan forske på kultur og ny teknologi? Om metodiske perspektiver i studier av relasjonen mellom mennesker og maskiner - Stuedahl, Dagny (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
The article discusses how Actor-Network Theory (ANT) delivers valuable perspectives for ethnological and folkloristic studies in the emerging research field culture and technology. By pinpointing to some main concepts in ANT, the article discusses shortly resemblances and differences between the ANT focus on communication, and the understanding of communicational processes in different periods of nordic cultural studies. The article highlights the ANT focus on negotiation as a relevant perspective on cultural processes as well, and proposes to explore the notion of tradition in relation to the ANT concepts translation, inscription and enrolment.